2020
DOI: 10.3390/jcm9041166
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Older Adults Who Were Early Adopters of Medical Cannabis in the Florida Medical Marijuana Use Registry

Abstract: Use of medical marijuana is increasing in the United States and older adults are the fastest growing user group. There is little information about the characteristics and outcomes related to medical marijuana use. This study is a descriptive analysis of older adults (aged ≥50 years old) who were early adopters of a medical marijuana program in the U.S. state of Florida. Per state legislation, initial and follow-up treatment plans were submitted to the University of Florida College of Pharmacy. Data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…The effects of THC on cognition, including euphoria, sedation, and dissociative effects, are typically thought to be responsible for pain relief, which is a primary reason for medical cannabis and cannabinoid use 62,75,83 . THC use, however, is also associated with long‐term memory deficits 84,85 .…”
Section: Adverse Drug Events With Natural and Synthetic Cannabinoidsmentioning
confidence: 99%
“…The effects of THC on cognition, including euphoria, sedation, and dissociative effects, are typically thought to be responsible for pain relief, which is a primary reason for medical cannabis and cannabinoid use 62,75,83 . THC use, however, is also associated with long‐term memory deficits 84,85 .…”
Section: Adverse Drug Events With Natural and Synthetic Cannabinoidsmentioning
confidence: 99%
“…Reblin and colleagues [12] investigated MMJ use practices among Florida MMJ glioma patients. Brown et al [3] analyzed the data of adults aged 50 and older who were early adopters of MMJ in Florida and found many were using MMJ to treat musculoskeletal disorders and spasms (48.4%), chronic pain (45.4%), cancer (15.5%), and psychological disorders (including PTSD) (23.2%). Almost 73% reported at least some improvement of their condition since initiating treatment.…”
Section: Medical Marijuana In Floridamentioning
confidence: 99%
“…The National Academies of Sciences, Engineering, and Medicine report [2] analyzed over 10,000 studies and concluded that cannabis and/or cannabinoids are effective for treating a variety of symptoms including chronic pain, nausea and vomiting, and stimulating hunger. Today, individuals use medical marijuana (MMJ) to treat a wide range of health conditions, including chronic pain, muscle spasms, anxiety, depression, PTSD, insomnia, headache, nausea, appetite issues, cancer, and the adverse effects of cancer chemotherapy [1,[3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In eight states with medical cannabis laws (MCL) in 2014-2015, one third to more than one-half of medical cannabis registrants were aged 50+ (11). Of Florida's 7,548 registered medical users between August 2016 and July 2017, 58.9% were aged 50+; their chief medical complaints were musculoskeletal disorders and spasms, chronic pain, and PTSD or other psychological disorders (12). Our analysis of 2019 NSDUH data showed that 18.8% of past-year cannabis users aged 50+, compared to 11.3% of cannabis users aged 18-49, reported medical use.…”
Section: Introductionmentioning
confidence: 99%